Pemeriksaan Kesehatan Tekanan Darah Dan Glukosa Darah (DM) di Kecamatan Aek Kuo - SIPAYUNG, LEO PARDON; HARTONO, ADI (Universitas Teknokrat Indonesia, 2024)
This community service activity aims to provide free medical examination and treatment services to the community in Aek Kuo District to maintain their health. The solution to dealing with these problems is to conduct free examinations and treatment through the Community Service program. The target in the implementation of this community service is the community in the Aek Kuo District. The impact of this activity is to increase public awareness and knowledge in an effort to maintain their health. We limit the service capacity of our community service activities to 150 participants, which will be distributed evenly. During the examination, 29 people were found to have high blood pressure, 2 people had high blood sugar levels, and 99 people had uric acid levels exceeding normal limits. Overall, the community service activities went well and the most common health problem in the elderly is gout. So it is hoped that through this community service program, awareness about health, especially for the elderly, can be increased in order to achieve an optimal level of health.